Strategi Pembelajaran Di Perguruan Tinggi Pada Masa Pandemi Covid-19 - Puspitorini, Ferawaty (Jurnal Kajian Ilmiah, 2020)
Begin the Year 2020, the world back appalled by the spread of the virus dangerous and deadly. The public call it as a corona virus. The emergence of the virus allegedly originated from the City of Wuhan, capital of Hubei Province, China. This Virus was first reported to WHO on 31 December 2019. This research is qualitative descriptive which describe the activities of online learning at the University of Bhayangkara Jakarta Raya after the enactment of the entire learning activities conducted at home with online mode. The subject consists of 3 students and 2 lecturers of Universitas Bhayangkara Jakarta Raya. Data collection using interviews. Based on the results of wawanccara learning activities with the online mode at the University of Bhayangkara Jakarta Raya have been effective with utilizing E-Learning applications Ubhara Jaya, Zoom and Google Classroom. Constraints in the implementation of online learning, namely the problem of internet connection less support. Keywords: Online Learning, Pandemic, COVID-19 Abstrak Mengawali Tahun 2020, dunia kembali digemparkan dengan penyebaran virus berbahaya dan mematikan. Publik menyebutnya sebagai virus corona. Kemunculan virus tersebut ditengarai berawal dari Kota Wuhan, ibukota Provinsi Hubei, Tiongkok. Virus ini pertama kali dilaporkan ke WHO pada tanggal 31 Desember 2019. Penelitian ini merupakan deskriptif kualitatif yang mendeskripsikan kegiatan pembelajaran daring di Universitas Bhayangkara Jakarta Raya setelah ditetapkannya seluruh kegiatan pembelajaran dilaksanakan di rumah dengan mode daring. Subjek terdiri dari 3 mahasiswa dan 2 dosen Universitas Bhayangkara Jakarta Raya. Pengumpulan data menggunakan wawancara. Berdasarkan hasil wawanccara kegiatan pembelajaran dengan mode daring di Universitas Bhayangkara Jakarta Raya sudah efektif dengan memanfaatkan aplikasi E-Learning Ubhara Jaya, Zoom dan Google Classroom. Kendala dalam pelaksanaan pembelajaran daring yaitu masalah koneksi internet yang kurang mendukung. Kata kunci: pembelajaran online, masa pandemi, COVID-19